Exploration of human xylosyltransferase for chemoenzymatic synthesis of proteoglycan linkage region. Issue 15 (25th March 2021) - Gao, Jia; Lin, Po-han; Nick, Setare Tahmasebi; Liu, Kunli; Yu, Kefei; Hohenester, Erhard; Huang, Xuefei
Abstract : Human xylosyl transferase can effectively install a xylose stereospecifically onto a peptide backbone on mg scales paving the way for efficient chemoenzymatic synthesis of proteoglycan glycopeptides and glycoproteins. Abstract : Proteoglycans (PGs) play important roles in many biological processes including tumor progression, cell adhesion, and regulation of growth factor activities. With glycosaminoglycan chains attached to the core proteins in nature, PGs are highly challenging synthetic targets due to the difficulties in integrating the sulfated glycans with the peptide backbone. To expedite the synthesis, herein, the utility of human xylosyltransferase I (XT-I), the enzyme responsible for initiating PG synthesis, has been explored. XT-I was found to be capable of efficiently installing the xylose unit onto a variety of peptide structures on mg scales. Furthermore, an unnatural sugar, i.e., 6-azidoglucose can be transferred by XT-I introducing a reactive handle onto the glycopeptide for selective functionalization. XT-I can be coupled with β-4-galactosyl transferase-7 for one pot synthesis of glycopeptides bearing galactose-xylose disaccharide, paving the way toward efficient chemoenzymatic synthesis of PG glycopeptides and glycoproteins.